Cultural branding: Development of culture-based tourism village towards sustainable tourism - Kristian Suhartadi Widi Nugraha; Ika Barokah Suryaningsih; Cempaka Paramita; Gusti Ayu Wulandari; Fajar Destari; Devina Widya Cahyani; Mohamad Fikri Hafiyan (Universitas Muhammadiyah Malang, 2024)
Kamal Village in Arjasa District, Jember Regency, East Java, has cultural and historical tourism potential through the Duplang Site, Klanceng Site, Ta' Butaan folk art, and Kadisah traditional rituals. This great tourism potential can be developed to promote Kamal Village as a culture-based tourism village. Through a participatory rural appraisal approach involving village-owned businesses, the Tourism Appreciation and Tourism Awareness Group, the Youth Organization of Kamal Village, and collaboration with the Jember Regency Tourism and Culture Office, the community service team assisted in the form of organizational assistance (institutional strengthening), event management training, and strengthening the promotion and branding activities. The results of this community service are expected to strengthen the cultural branding of Kamal Village towards sustainable tourism to realize sustainable and positive economic, social, and environmental impacts for related stakeholders.